THE REPRESENTATION OF AQJ'S CAR ACCIDENT ON SEPTEMBER 8 AND THE PARTIES INVOLVED - Ainun, Ismy Fauziah (2014)
This study entitled The Study of The Jakarta Globe's Representation in Reporting AQJ's Car Accident on September 8 and The Parties Involved: The Study of Critical Discourse Analysis. This study aims to revealthe representation of AQJ's car accidenton September 8and the parties involvedin the articles by the Jakarta Globe. This study used aqualitative descriptive method. The theory used in this study is Systemic Functional Grammar (SFG) approach proposed by Halliday (2004) covering transitivity and nominalization, and the Critical Discourse Analysis (CDA) proposed by Norman Fairclough (2003) as well as the social event identification. The findings of this study suggest that the newspaper represents the accident asan inevitable event. The suspects tend to be represented as being guilty. Meanwhile, the government seems to be represented intensively as the sympathetic and reliable party, and the victims tend to be represented as the unfortunate citizens who have to endure the result of the accident. Those representations lead to the conclusion that the newspaper is on the government's side. Penelitianiniberjudul The Study of The Jakarta Globe's Representation in Reporting AQJ's Car Accident on September 8 and The Parties Involved: The Study of Critical Discourse Analysis. Penelitian ini bertujuan untuk mengungkap representasi kecelakaan mobil oleh AQJ pada tanggal 8 September dan pihak-pihak yang terkait dalam artikel Jakarta Globe. Penelitian in imenggunakan metode qualitif deskriptif. Teori yang digunakan dalam penelitian ini adalah Systemic Functional Grammar (SFG) yang dikemukakan olehHalliday (2004) mencakup transitivity dan nominalisasi, dan the Critical Discourse Analysis (CDA) yang dikemukakan oleh Norman Fairclough (2003) dalam social event identification. Hasil dari penelitian ini menjelaskan bahw aartikel dalam Jakarta Globe merepresentasikan kecelakaan mobil sebagai suatu kejadian yang tidak bisa dihindari. Pelaku cenderung direpresentasikan sebagai seseorang yang bersalah. Sementaraitu, pemerintahan direpresentasikan sebagai pihak yang bersimpati dan dapat dipercaya dan korban cenderung direpresentasikan sebagai masyarakat yang kurang beruntung yang harus menanggung hasil dari kecelakaan. Dari keseluruhan representasi dapat disimpulkan bahwa Koran Jakarta Globe berada di pihak pemerintah.